2018
DOI: 10.1016/j.agwat.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Runoff, nutrients, sediment and salt yields in an irrigated watershed in southern Navarre (Spain)

Abstract: The environmental impact of irrigated agriculture on water quality was assessed in Landazuria watershed (Navarre, northeast Spain), a 479.5 ha watershed with 53% of irrigated agricultural land. In the framework of a long-term monitoring program, precipitation and discharge were measured at 10-minutes intervals and compound daily water samples were collected during the agricultural years (September to August) 2007-2016, and analysed for nitrate (NO 3-), phosphate (PO 4 3-), sediment and total dissolved solids (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…Agricultural management in these watersheds is the typical for the different land uses in the region, since the objective of the network is to adequately characterize the behaviour of these watersheds under standard management conditions. Previous works have described the physical and agronomic characteristics of each watershed, along with the quality of the water generated in terms of suspended sediment, nitrate or phosphate (Casalí et al, 2008(Casalí et al, , 2010Merchán et al, 2018). In addition, other studies have been performed in these watershed.…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural management in these watersheds is the typical for the different land uses in the region, since the objective of the network is to adequately characterize the behaviour of these watersheds under standard management conditions. Previous works have described the physical and agronomic characteristics of each watershed, along with the quality of the water generated in terms of suspended sediment, nitrate or phosphate (Casalí et al, 2008(Casalí et al, , 2010Merchán et al, 2018). In addition, other studies have been performed in these watershed.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that N deficiency played an important role in this transition. On the other hand, pollution processes in agroecosystems with irrigated croplands, including nitrate (NO 3 − ), phosphate (PO 4 3− ), and total dissolved solids (TDS), present a high degree of variation owing to agricultural management (including crop surfaces, irrigation and fertilization rates) [7]. Hydrologic and geomorphic studies in natural forestry areas and forest plantations are necessary to assess the impact of natural-and human-induced heterogeneities, such as climate variability, vegetation reconstruction, abandoned fields and timber activities, and thus to propose best management practices.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the use of elevated fertilizer doses (Pardo et al, 2017;Poch-Massegú et al, 2014) to increment crop yield and poor support conservation practices (Panagos et al, 2015) are still a common practice in agricultural areas. Both produce a direct impact on water quality through the nitrogen surplus and soil erosion, but the latter also produces an indirect impact contributing to soil degradation through the removal of the topsoil and finest fraction of soils, where organic matter and nutrients are concentrated (García-Ruiz et al, 2015;Merchán et al, 2018), which usually entails a crop yield decline (García-Ruiz et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, soil erosion in semiarid agricultural areas is usually high (Durán Zuazo et al, 2006), and as agricultural soils are rich in nitrogen (García-Ruiz et al, 2015;Merchán et al, 2018), the nitrogen transport associated to soil erosion is noteworthy, which leads to the consideration of the sediment cycle.…”
Section: Main Objectivesmentioning
confidence: 99%
See 1 more Smart Citation